Joint Detection and Decoding of Polar Coded 5G Control Channels - Jalali, Amin; Ding, Zhi (IEEE transactions on wireless communications, 2020)
The recent release of the cellular standard known as 5G New Radio (5G-NR) has adopted polar codes for error protection in the physical downlink control channel (PDCCH). We develop a novel joint detection and decoding algorithm for 5G multiple-input multiple-output (MIMO) transceivers to achieve robustness against practical obstacles including channel state information (CSI) errors, noise, interferences, and pilot contamination. To optimize the performance of PDCCH detection, we incorporate the polar code information during signal detection by transforming the Galois field code constraints into the complex signal field. Specifically, our novel joint linear programming (LP) formulation takes into consideration the transformed polar code constraints. Our proposed detector can also be integrated with effective successive cancellation list (SCL) decoders to deliver superior receiver performance and improve the computational efficiency compared to turbo approach joint detection decoding design. Moreover, similar to 4G-LTE, each active user equipment (UE) must blindly detect its own PDCCH in the downlink search space. We further introduce a metric readily available at the detector that can be used to eliminate most of wrong PDCCH candidates before sending them to the decoder and therefore, improve the computational efficiency of PDCCH blind detection for 5G-NR.